Evaluation of Elemental and Chemical Compositions of Some Fuelwood Species for Energy Value - A. M. Dadile; O. A. Sotannde; B. D. Zira; M. Garba; I. Yakubu (International Journal of Forestry Research)
Fuelwood species are a crucial part of the ecosystem; they provide energy for cooking, heating, and lightening for both domestic and industrial uses. As a result of their value, there is a need for frequent evaluation of elemental and chemical compositions for management and conservation purposes. Since fuelwood is the most common and cheapest source of energy in both rural and urban areas in northern Nigeria, the study area is facing serious challenges due to indiscriminate felling of trees for energy use, irrespective of species quality for combustion. Therefore, ten fuelwood species were selected for this study. The selected trees were harvested at Dbh level, replicated three times. Four fuel materials were obtained from each tree sample; these include wood without bark (100% wood sample), wood with 5% bark inclusion, wood with 10% bark inclusion, and whole bark samples and they were evaluated for their inherent elemental and chemical compositions by employing ASTM and TAPPI methods. The results showed that there were significant differences in the tree species and fuel material types obtained from all the ten fuelwood species used. The results of carbon content ranges from 49.54% in A. sieberiana to 50.98% in A. leiocarpus. Meanwhile, the addition of 5% and 10% bark reduces carbon content of wood by 1.25% and 2.74%, respectively. Nitrogen content ranged from 0.31% in A. leiocarpus to 1.00% in A. sieberiana. Among the fuel materials used, isolated bark contained approximately 0.45% nitrogen content compared with wood without bark. Among the tree species, hydrogen content ranged from 3.99% in P. reticulatum to 4.66% in C. arereh. The variation in sulphur contents ranged from 0.24% in C. arereh to 0.93% in A. sieberiana. Lignin content ranged from 10.68% in A. sieberiana to 25.39% in A. leiocarpu and extractive content values ranged from 7.31% in A. leiocarpus to 19.33% in P. reticulatum. Meanwhile, the fuelwood species observed in this study with higher percentage of carbon, hydrogen, and lignin and lower nitrogen and sulphur and extractive content possessed quality fuel value and thereby were encouraged to be incorporated in fuelwood plantation establishment programs (A. leiocarpus, C. molle, C. arereh, and B. aegyptiaca). Lower energy fuelwood species should be allowed for environmental amelioration and carbon sequestration. However, bark contents should be removed for better heating and low ash production during combustion.